Cathepsin B, H and L inhibitors as cell proliferating agents: design, synthesis, computational and pharmacological studies of some novel 2-(2-naphthoyl)-6, 6-dimethyl-3-aryl-2, 3, 6, 7-tetrahydrobenzofuran-4(5H)-ones. Issue 41 (8th April 2016) - Raghav, Neera; Jangra, Suman; Kumar, Ajay; Bhattacharyya, Shalmoli; Wadhwa, Deepak; Sindhu, Jayant
Abstract : A novel series of 2-(2-naphthoyl)-6, 6-dimethyl-3-aryl-2, 3, 6, 7-tetrahydrobenzofuran-4(5 H )-one derivatives synthesized and structure confirmed by X-ray crystallography have been evaluated as inhibitors to cathepsins B, H and L as well as cell proliferating agents. Abstract : Elevated levels of cathepsins B, H and L in disease conditions such as inflammation and cancer accentuate the need for design, synthesis and pharmacological evaluation of new compounds, keeping in view target-specific therapy. The present work describes the one pot multicomponent synthesis of some novel 2-(2-naphthoyl)-6, 6-dimethyl-3-aryl-2, 3, 6, 7-tetrahydrobenzofuran-4(5 H )-ones in good yields. The synthesized compounds were analysed by spectral and X-crystallographic studies and have been found to be potential inhibitors to cathepsins B, H and L. The extent of inhibition varied with the substitution. Among the synthesized compounds, nitro-substituted compound1d has been evaluated as most inhibitory to cathepsin H, however fluoro-substituted compound1f was the best inhibitor of cathepsin B and cathepsin L. The compounds have been found more selective towards cathepsin L. In vitro inhibition studies correlate well when tested using MTT assay on HepG2 cells, a hepatocellular carcinoma cell line. The results validated by in silico studies performed with iGemDock predicted that among the synthesized compounds, 1d experiences the highest affinity for cathepsin B and H sites, whereas1f has the highest affinity to cathepsin L.